2021
DOI: 10.1177/14777606211001074
|View full text |Cite
|
Sign up to set email alerts
|

A novel recycled polyethylene terephthalate/polyamide 11 (rPET/PA11) thermoplastic blend

Abstract: This work explores a novel blend of recycled polyethylene terephthalate/polyamide 11 (rPET/PA11). The blend of rPET/PA11 was introduced to enhance the mechanical properties of rPET at various ratios. The work’s main advantage was to utilize rPET in thermoplastic form for various applications. Three different ratios, i.e. 10, 20 and 30 wt.% of PA11 blend samples, were prepared using a twin-screw extruder and injection moulding machine. The mechanical properties were examined in terms of tensile, flexural and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…9 In general, voids tend to modify the scatter of the results when comparing with a reference specimen without voids, and decrease the mechanical properties. 34 In addition, recycled PET could not present values of flexural strength closed to the virgin PET as showed in work of Khan et al 35 that reported a value of 27.9 MPa with the use of a twin extruder, that may increase the degradation of the properties. 35,36…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…9 In general, voids tend to modify the scatter of the results when comparing with a reference specimen without voids, and decrease the mechanical properties. 34 In addition, recycled PET could not present values of flexural strength closed to the virgin PET as showed in work of Khan et al 35 that reported a value of 27.9 MPa with the use of a twin extruder, that may increase the degradation of the properties. 35,36…”
Section: Resultsmentioning
confidence: 93%
“…34 In addition, recycled PET could not present values of flexural strength closed to the virgin PET as showed in work of Khan et al 35 that reported a value of 27.9 MPa with the use of a twin extruder, that may increase the degradation of the properties. 35,36…”
Section: Resultsmentioning
confidence: 93%
“…2,3 The heavy use of synthetic fibre composites raised many environmental issues. 4,5 From the last few decades, natural fibres are the most commonly used reinforcement in polymer composites. It is because of their benefits such as being eco-friendly, cheap, light in weight and good strength.…”
Section: Introductionmentioning
confidence: 99%